A Four-channel TEA N2 laser controlled by a multistage spark gap - Tou, T.Y.; Kwek, K.H.; Chin, Oi Hoong (1993)
A four-channel nanosecond transversely excited atmospheric (TEA) N2 laser controlled by a simple and cost effective multistage spark gap which offers a high flexibility in varying the time sequence of the laser pulses from over 100 ns to as low as 5 ns is described. The delays between these laser pulses depend mainly on two important spark gap breakdown parameters: the charging voltage and their respective gap separations. The jitters between these laser pulses are observed to be independent of the initial ignition of the multistage spark gap-hence a precision and very fast triggering technique that is usually crucial for such work can be dispensed with.